2016
DOI: 10.1104/pp.16.00154
|View full text |Cite
|
Sign up to set email alerts
|

The ERF11 Transcription Factor Promotes Internode Elongation by Activating Gibberellin Biosynthesis and Signaling

Abstract: The phytohormone gibberellin (GA) plays a key role in promoting stem elongation in plants. Previous studies show that GA activates its signaling pathway by inducing rapid degradation of DELLA proteins, GA signaling repressors. Using an activation-tagging screen in a reduced-GA mutant ga1-6 background, we identified AtERF11 to be a novel positive regulator of both GA biosynthesis and GA signaling for internode elongation. Overexpression of AtERF11 partially rescued the dwarf phenotype of ga1-6. AtERF11 is a mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 61 publications
2
62
1
Order By: Relevance
“…However, when we examined growth in more detail in this study, we could observe that the younger leaves of rap2.6L had a reduced size, possibly through decreased cell division. The overexpression of ERF11 caused a decreased rosette size in this and a previous study (Dubois et al , 2015), suggesting that ERF11 is a negative regulator of growth, whereas another study reported that the overexpression of ERF11 resulted in the promotion of internode elongation (Zhou et al , 2016). Even though a contrasting phenotype was observed, a link between ERF11 and the GA2‐OX/DELLA pathway was established.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, when we examined growth in more detail in this study, we could observe that the younger leaves of rap2.6L had a reduced size, possibly through decreased cell division. The overexpression of ERF11 caused a decreased rosette size in this and a previous study (Dubois et al , 2015), suggesting that ERF11 is a negative regulator of growth, whereas another study reported that the overexpression of ERF11 resulted in the promotion of internode elongation (Zhou et al , 2016). Even though a contrasting phenotype was observed, a link between ERF11 and the GA2‐OX/DELLA pathway was established.…”
Section: Discussionsupporting
confidence: 60%
“…We could identify five growth repressors (ERF6, ERF8, ERF9, ERF11, and ERF98) and five growth enhancers (ERF2, ERF59, RAP2.6L, STZ, and WRKY6) (Table EV2). Leaf growth under control conditions has previously been quantified for mutant lines of ERF2, ERF5, ERF6, ERF8, ERF11, RAP2.6L, and WRKY15 (Vanderauwera et al , 2012; Dubois et al , 2013, 2015, 2017; Zhou et al , 2016). RAP2.6L has, for example, been shown to play a role in the regulation of the division of pith cells (Asahina et al , 2011), but no clear growth phenotypes have previously been observed in rap2.6L mutants or RAP2.6L overexpression lines (Krishnaswamy et al , 2011; Liu et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the DELLA proteins are central repressors of GA responses (Sun, 2010, 2011; Plackett et al, 2014), and accumulating evidence suggested that DELLA proteins play important roles in ethylene-mediated plant growth and development processes through interactions with some regulatory factors in ethylene signaling pathway, such as CTR1 (CONSTITUTIVE TRIPLE RESPONSE1), EIN3/EIL1 (ETHYLENE INSENSITIVE 3/EIN3-LIKE 1), RAP 2.3 (RELATED TO APETALA 2.3), and ERF11 (ETHYLENE RESPONSE FACTOR 11) (Achard et al, 2003, 2007; Pierik et al, 2009; An et al, 2012; Luo et al, 2013; Marín-de la Rosa et al, 2014; Zhou et al, 2016). Therefore, we proposed that DELLA proteins may be involved in the sex differentiation of cucumber coupled with GA and ethylene in a collaborative regulation at the protein level, since the expressions of four DELLA homologs in cucumber, CsGAIP, CsGAI1, CsGAI2 , and CsGAI3 (Zhang et al, 2014a), had no change after GA 3 treatment (Supplementary Tables S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…The AP2/ERF proteins contain four major subfamilies: DREB, ERF, AP2 and RAV, each harbouring unique conserved motifs (Nakano et al ., ). A number of studies reveal that the ERF subfamily members in various plant species, acting as either transcriptional activators or repressors, play a pivotal role in regulation of a range of physiological and biological processes, including internode elongation (Zhou et al ., ), root growth (Jung et al ., ), trichome formation (Sun et al ., ), fruit ripening (Yin et al ., ), hormone signal transduction (Rashotte et al ., ), secondary metabolism and biotic stress response (Zeng et al ., ; Zhu et al ., ). Accumulating evidence demonstrate that ERFs are also implicated in response to abiotic stresses, including submergence or hypoxia (Xu et al ., ), heavy metal (Lin et al ., ), drought (Jung et al ., ) and high salinity (Yao et al ., ).…”
Section: Introductionmentioning
confidence: 99%